Beyond Core–Shell Micellar Structures: Complex Structures in Simple Surfactants - Henrique Musseli Cezar; Victoria Ariel Bjørnestad; Sylvain Prévost; Reidar Lund; Michele Cascella (Small Structures)
Small‐angle X‐ray/neutron scattering (SAXS/SANS) techniques provide valuable nanostructural information of self‐assembling molecules. However, extracting the information from these experiments can be a challenging task, usually relying on predetermined assumptions. Conventional models for surfactant micelles consider a core–shell structure with a hydrophobic tail encapsulated by the hydrophilic part. This approach is successful in many cases but can fail even for common surfactants such as Triton X‐100 (TX‐100). SAXS and SANS combined with Metainference molecular simulations are employed to investigate TX‐100 assemblies, showing how more complex models, with diffuse core–shell boundaries, multilayering, and polydispersity, are needed to explain the aggregation. This is the first time that Metainference is employed with SAXS and SANS simultaneously to obtain the structural ensemble of assemblies. Compared to regular micelles formed by chemically similar C12EO10 molecules, the role of the hydrophobic core in micellization is discussed, finding that the relatively shorter and less hydrophobic tail of TX‐100 favors polymorphism.